(untitled) (Scientific journal of the Fergana State University, 2025)
Quantum mechanics is a fundamental and fundamental science in modern physics, and its concepts allow us to explain many natural phenomena. Its methodology plays a very important role in teaching, because quantum mechanics often seems to students as an abstract and complex science. Solving problems develops not only theoretical knowledge, but also mathematical skills. This article discusses effective methods for solving problems in practical lessons on quantum mechanics